2005
DOI: 10.1254/jphs.fpj04044x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Fourteen Chemical Agents Used in Dental Practice to Induce Chromosome Aberrations in Syrian Hamster Embryo Cells

Abstract: Abstract. To assess the genotoxicity of 14 chemical agents used in dental practice, the ability of these agents to induce chromosome aberrations was examined using Syrian hamster embryo (SHE) cells. Statistically significant increases in the frequencies of chromosome aberrations were induced in SHE cells treated with 7 of 10 chemical agents used as endodontic medicaments, that is, carbol camphor, m-cresol, eugenol, guaiacol, zinc oxide, hydrogen peroxide, and formaldehyde. The other 3 chemical agents, that is,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 17 publications
(23 reference statements)
1
36
1
1
Order By: Relevance
“…Many oral disinfectants are used in dental clinics and povidone iodine (PVD-I), benzethonium chloride (BEC), and benzalkonium chloride (BAC) are commonly the major components of oral disinfectants [1][2][3][4][5][6][7] . PVD-I is a major component of Isodine ® gargle, which contains 7% PVD-I as an active ingredient and other additives, such as ethanol, menthol, methyl salicylate, glycerin, sodium saccharin, disodium phosphate, citric acid, eucalyptus oil, and thymol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many oral disinfectants are used in dental clinics and povidone iodine (PVD-I), benzethonium chloride (BEC), and benzalkonium chloride (BAC) are commonly the major components of oral disinfectants [1][2][3][4][5][6][7] . PVD-I is a major component of Isodine ® gargle, which contains 7% PVD-I as an active ingredient and other additives, such as ethanol, menthol, methyl salicylate, glycerin, sodium saccharin, disodium phosphate, citric acid, eucalyptus oil, and thymol.…”
Section: Discussionmentioning
confidence: 99%
“…Many different oral disinfectants have been used to treat teeth and soft tissues in the dental clinic [1][2][3][4][5][6][7] . Oral disinfectants consist of a solution with a mix of components.…”
Section: Introductionmentioning
confidence: 99%
“…26 In another study, Hikiba et al assessed the effect of iodine and iodoform on chromosome aberrations using Syrian hamster embryo (SHE) cells, and found that iodine induced chromosome aberrations and iodoform induced no genotoxicity. 27 Using the comet assay, Muller et al found no chromosomal damage. 28 In another study, Hedayati et al showed that incubation of lymphocytes with iodine increased micronuclei frequency and induced genotoxicity.…”
Section: Iodine Potassium Iodide (Iki)mentioning
confidence: 99%
“…30 Formaldehyde and m-cresol still show genotoxic effects to mammalian cells in other studies using SHE. 31 It is clear this area needs further study.…”
Section: Genotoxicity and Carcinogenicitymentioning
confidence: 99%